Ouverture pour cause d’inventaire. Figures et significations de l’exhaustivité en exposition - Dulguerova, Elitza (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2018)
This article examines how exhaustiveness serves as a guiding principal for certain exhibitions, and particularly as a means of critiquing selection as the dominant method of promoting specific artworks, artists, and movements. It begins by outlining the possible genealogies of this attitude in the history of exhibition forms, as well as artists’ experiments with these forms. It then focuses on the work of curators Michael Fehr, Véronique Souben, and Rebecca Duclos and David K. Ross, who, in different contexts, have used notions of inventory and storage to exhaustively present collections. These practices represent strategies of resistance and critique whose contemporary relevance needs to be evaluated alongside their strengths and weaknesses.